Maddenin Yapısı ve Özellikleri" Ünitesindeki Öğrenci Kazanımlarının Bilişsel Alan Basamaklarında Gerçekleşme Düzeyleri ve Farklı Değişkenlere Göre Analizi - Canpolat, Erdal; Aksakal, Gizem (Fırat University, 2018)
Bu çalışmada, “Maddenin yapısı ve özellikleri” ünitesi ile ilgili araştırmacı tarafından hazırlanan başarı testindeki sorulara 8. sınıf öğrencilerinin verdikleri cevaplara göre; farklı değişkenler (cinsiyet, ailenin gelir durumu, anne eğitim, baba eğitim durumu ve yerleşim birimi) için öğrencilerin bilişsel alan basamaklarında gösterdikleri başarı, kalıcılık ve ayrıca bu ünite için seçilen kazanımların gerçekleşme durumlarının belirlenmesi amaçlanmıştır. Çalışma Elazığ’da 9 il merkezi, 6 ilçe ve 2 köy ilköğretim okulunda gerçekleştirilmiştir. Örneklemi 8. sınıftan 584 öğrenci oluşturmuştur. Analizler yapılırken SPSS programı kullanılmıştır. 8. sınıflar için kavrama basamağındaki kazanımlar, doğru cevap yüzdeleri belirlenen %70 sınırının altında kaldıkları için kazanılmamışlardır. Bilgi ve uygulama basamağında ise doğru cevap yüzdeleri %70 sınırının üstünde oldukları için kazanılmışlardır. Kalıcılığın en yüksek olduğu bilgi basamağında şehirde yaşayan, aile gelir durumu 2250 TL üzeri olan, anne eğitim durumu diğer grubunda; baba eğitim düzeyi üniversite mezunu olan kız öğrencilerden oluşan grup en başarılı grup olmuştur.

In this study; according to the answers given by the 8th grade students to the questions in the success test prepared by the researcher about the "Structure and Properties of Matter " unit; determining of success and permanence offered by the students for cognitive levels is aimed for variables of gender, income level of students’ families, education levels of the students’ mothers, education levels of the students’ fathers and dwelling place of the students and also according to the correct answers, determining of realization levels of selected acquisitions for units which are mentioned above for cognitive levels is aimed. The study was applied for 9 school in Elazığ city center, 6 school in county center and 2 school in villages. 584 students from class 8 students constitute of the sample. SSPS has been used for analysis Acquisitions for the understanding steps wasn't acquired for classes 8 because of remaining below limit of %70 which is set in accordance with the correct answers. For the knowledge step, has been acquired owing to being above limit of %70 which is set for the correct answers. Women students who are living in city center, have family whose income above 2250 TL and whose mothers’ education level is other and fathers have university graduate have become the most successful group for knowledge step which has the highest permanence.
Levels of Student Achievements in Cognitive Field Stages of Structure and Properties of Matter Unit and Analysis According to Different Variables